PENGATURAN KONTRAK INTI PLASMA DALAM PEMBERDAYAAN USAHA PERKEBUNAN YANG PATUT DAN ADIL - Adinda Prisca Anugerah Puteri; Faizal Kurniawan (Universitas Airlangga, 2015)
Partnership relation as one of work relation between the farmer as the representative of micro business and main company as macro business as the owner, science and technology based on a deal is known as plasma core partnership relation. In it's implementation, many problems happened and resisted which may trigger disadvantages especially for the farmer. Therefore it is very important to pay our attention about the validaty and basics contract principle in the implementation of plasma core partnership contract. The goverments support actively or passively takes also a role in enforcing norms and regulations of the contract, so that the purpose of every side can be reached and the goals of every party could be secured as well.